Mycobacterium avium complex pulmonary disease: new epidemiology and management concepts. Issue 2 (April 2018) - Lande, Leah; George, Jason; Plush, Theodore
Abstract : Purpose of review: The prevalence of Mycobacterium avium complex (MAC)-related pulmonary disease has been increasing because of environmental factors, changes in organism virulence, and evolving host susceptibility. Treatment is often complicated by adverse effects, development of drug resistance, and refractory disease, with recurrence rates as high as 25–45%. Recent findings: Aerosolization of water, soil, or dusts are the likely sources of MAC-related pulmonary disease in susceptible individuals. The management of MAC-related pulmonary disease requires a multimodality approach, including antimicrobial therapy in appropriate patients, employment of mucus clearance techniques, instituting changes in the individual's home environment and personal habits to reduce environmental exposure to MAC, prevention of reflux, and maintenance of a healthy body weight. When the standard treatment for MAC-related pulmonary disease is not possible because of drug intolerance, antibiotic resistance, or progression of disease, second-line agents such as inhaled amikacin, clofazimine, bedaquiline, and delamanid must be considered, despite limited experience and few studies to guide their use. Summary: Individuals who have proven to be susceptible to MAC-related pulmonary disease should institute measures to reduce exposure to environmental sources of infection. Further research is needed to assess the impact of such preventive strategies on the incidence of new infection and disease recurrence. The efficacy of new medications for MAC-related pulmonary disease and their use in different combinations also requires further study.